Complex symplectic contractions and 3d mirrors - Dancer, A; Grimminger, JF; Martens, J; Zhong, Z (Springer, 2024)
We propose magnetic quivers for the complex-symplectic contraction spaces, which are related to implosions and have a natural interpretation in terms of the Moore-Tachikawa category. We use 3-d mirrors to provide computational checks.